(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to explain the audit procedures regarding the change in foreign currency exchange rates in the branches of foreign companies and the possibility of applying International Accounting Standard No. (21) AIS in Iraq and to multinational companies. The reflection of the application of International Accounting Standard (21) AIS on the audit procedures of auditing companies in the sector. Private and Financial Supervision Bureau for the year 2021 By preparing appropriate audit procedures to clarify and audit the treatments for differences resulting from the adoption of International Accounting Standard No. (21) AIS. The research reached a set of conclusions, namely compatibility with international standards, improving the accuracy of financial reports, reducing the risks of volatility, the impact of financial transfers, financial risk management, the impact of market fluctuations, the impact of global economic changes, the importance of internal auditing, and enhancing the efficiency of external auditing.